Catalysing decentralised renewable energy investment in Nigeria: investor-focused risk evaluation and de-risking strategies - Abba, Yahajja Zara Ibrahim; Balta-Ozkan, Nazmiye; Drew, Gillian H. (Elsevier, 2025)
Scaling up private investment in Decentralised Renewable Energy (DRE) is crucial for achieving universal electricity access in sub-Saharan Africa. Tailored de-risking actions based on investors' risk perceptions can facilitate investment. However, current literature provides a fragmented perspective of investor-specific DRE investment risks. Through a multi-step participatory approach involving an online survey, focus groups, and interviews, 40 multidimensional risk factors across six categories were evaluated using the analytical hierarchy process, to establish their significance among four investor groups: development finance institutions, domestic finance institutions, developers, impact investors. Overall, economic and financing risk categories emerged as most critical, while social and environmental risks were least prioritised. However, risk factor priorities varied among different investor groups, highlighting key mutual high-priority risk factors amounting to 37–58 % of risk weighting including currency volatility, low access to low-cost capital, revenue risk, and insecurity. Limited awareness of existing risk mitigation practices, cultural and behavioural barriers to energy use, and path dependence were identified as influential risk drivers. Evidence-based risk mitigation strategies such as priority sector lending mandates, portfolio aggregation, stronger policy implementation, social interventions, collaboration, and capacity development are recommended to facilitate DRE investment. This study serves as a reference for decision-makers to prioritise actions for catalysing DRE investment.
Keywords: Decentralised renewable energy investment risks; Investment risk evaluation; Risk mitigation; Holistic risk management; Analytical hierarchy process